Mendorong Kepercayaan Diri Anak Madrasah Diniyah Sullamul Hidayah Melalui Seminar dan Pelatihan Public Speaking - Nur Hamda Sa’idah; Widya Arum Lestari; Muhammad Yusuf Saifullah; I’in Ustadhiyah; Sokhi Zuhrotunnisa; Maulidia Putri Anggraini; Susilo Wati; Riska Maulina; Hafidha Asni Akmalia (Lembaga Pengembangan Kinerja Dosen, 2024)
Public speaking is an ability that a person has to be able to speak in public with the aim of conveying an idea or information. Public speaking is an important skill to have in this day and age. However, in reality, public speaking becomes a scary thing for some people. This is due to feelings of anxiety, fear, nervousness, and lack of confidence in their own abilities. The existence of public speaking seminars and training is expected to increase self-confidence and eliminate feelings of fear when faced with such situations. The activity entitled